Transmission of pathogens within the commonly consumed vegetables: Bangladesh perspective (Stamford Journal of Microbiology, 2019)
Fresh vegetables and fruits are prime source of fiber, vitamins and minerals in our daily diet. Nevertheless, raw vegetables act as a vector for transmitting pathogenic microbes and the majority of diseases are spread by the fecal-oral route at different point of harvesting, post harvesting, during transportation and storage conditions. Contaminated water, carrier materials, and unhygienic handlers are the crucial gateway for disease causing microbes in fresh vegetables. Recently Listeria spp., E. coli, and Salmonella spp. associated outbreak evident in mixed vegetables salad and other vegetable samples also showed pathogenic proliferation to some extent. Children are the major risk group and according to World Health Organization, their mortality rate is high due to food borne infections. In Bangladesh, the situation is more alarming in terms of pathogenic proliferation in raw vegetables. A lot of researches have been conducted in recent years on fresh vegetables and a wide range of vegetables are found to harbor pathogenic microorganisms inclusive of drug resistant bacteria which may affect the measures to combat harmful pathogens. Additionally, phytotoxic, natural contaminants and pesticides are also found to reside in raw vegetables which may be life threatening for both human and animal health as these particles magnify when we repeatedly consume them. The current review focus on the possible intervention of potential contaminants in the vegetable items and possible public health risks associated with their consumption along with a general guideline to combat contamination of fresh vegetables.Stamford Journal of Microbiology, Vol.8(1) 2018: 46-49